The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.2147/jmdh.s459013
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Medical Care Service Motivation Among Medical Staff in Beijing, China: the Role of Institutional Support

Yutong Yang,
Mingyu Gu,
Xingming Li
et al.

Abstract: Background Home-based medical care services (HMCS) play a crucial role in China’s response to an aging population. Given the scarcity of quantitative research on motivating medical staff in relevant institutions, this study aimed to explore the impact of institutional support on motivating the provision of HMCS. Methods The medical staff involved in this study originated from seven community health service centers in Beijing. We utilized a self-designed questionnaire to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…
We are writing to acknowledge the recent publication titled "Home-Based Medical Care Service Motivation Among Medical Staff in Beijing, China: The Role of Institutional Support" by Yutong Yang et al published in Journal of Multidisciplinary Healthcare for its valuable contribution to health research. 1 The study, which achieved a significant response rate of 66.12% among medical staff providing home-based medical care services, sheds light on the crucial role of institutional support in motivating healthcare professionals. The results showed that factors such as gender, position, job type, job title and years of experience were significantly associated with the provision of home medical care services.
…”
mentioning
confidence: 93%
“…
We are writing to acknowledge the recent publication titled "Home-Based Medical Care Service Motivation Among Medical Staff in Beijing, China: The Role of Institutional Support" by Yutong Yang et al published in Journal of Multidisciplinary Healthcare for its valuable contribution to health research. 1 The study, which achieved a significant response rate of 66.12% among medical staff providing home-based medical care services, sheds light on the crucial role of institutional support in motivating healthcare professionals. The results showed that factors such as gender, position, job type, job title and years of experience were significantly associated with the provision of home medical care services.
…”
mentioning
confidence: 93%